Jordan Inspection Reform : Lessons and Reflections - Aranki, Wafa; Shalan, Abeer (International Finance Corporation, Washington, D.C., 2017)
This paper summarizes the Jordanian experience in inspection reform to date, as overseen by IFC inspection reform project team; from providing an overview of the old system which triggered the need for reform, to explaining the reforms that were ultimately introduced. The authors describe the main challenges and lessons learned along the way, highlight the key results achieved by the project, and provide tips for better project management. The IFC team adopted a phased approach to reforming Jordan’s inspection process. The first phase (from 2007 to 2009) involved working with two pilot inspectorates: at the Ministry of Labor (MoL) and the Ministry of Environment (MoEnv). The second phase aims to replicate the reforms achieved at the Labor and Environment inspectorates in other inspectorates in Jordan, resolve any overlap or duplication issues and enhance information sharing and collaboration. By providing an overview of Jordan’s inspection reform process, the authors also aim to help others interested in pursuing inspection reforms in their own countries. The type, and scope, of inspection best practice should be carefully selected and customized to meet the requirements of the particular country in question.